Natural Resources and Rent Seeking Collusion in the Context of Dutch Disease - Anar Muradov (İstanbul İktisat Dergisi)
A new model is proposed in this paper by concentrating on the Dutch disease phenomenon along with rent seeking to demonstrate how a natural resource abundance (or a resource boom) affects resource movement and national income under rent seeking collusion in the energy sector. Dutch disease and rent seeking problems are studied under the natural resource curse theory which states that countries with natural resources usually perform worse than resource-poor countries. The resource movement is considered one of the effects of the Dutch disease. The resource movement occurrence or the movement of labor inputs from services to the energy sector depends on the degree of the boom. The boom may also facilitate rent seeking depending on its degree and the number of firms in the energy sector. In the duopoly case (n=2), a sufficiently small degree of the boom is necessary for rent seeking to be facilitated. However, with more than two firms (n>2), rent seeking activities will not happen because profits in collusion will be less than those without collusion in the model. Hence, the paper analyzes rent seeking by concentrating on duopoly results (n=2). The impact of the boom on national income depends on parameter values.